1997
DOI: 10.1080/03079459708419233
|View full text |Cite
|
Sign up to set email alerts
|

A long‐term study of Australian infectious bronchitis viruses indicates a major antigenic change in recently isolated strains

Abstract: The antigenic relationship among 36 IBV strains isolated between 1961 and 1994 from vaccinated and non-vaccinated chicken flocks was determined. Based on the reaction with nine monoclonal antibodies (MAbs) in ELISA and polyclonal chicken sera in western blotting, IBV strains clearly fell into two distinct antigenic groups. Nineteen IBV strains isolated between 1961 and 1994 from various locations were antigenically related, having common cross-reactive epitopes on the peplomer S, the nucleocapsid N and the mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 21 publications
1
23
0
3
Order By: Relevance
“…The S1 protein of IBV plays a key role in the induction of protective immune response against IBV and the variation in the S1 sequence is the major mechanism by which a new serotype emerges [2,12]. Phylogenetic analysis showed that the S1 sequences of JP8127, JP8443 and JP9758 are closely related to those of Australian viruses, which have a serotype distinct from the Massachusetts and Connecticut serotypes that have been commonly used as the vaccine [4,8]. Similarly, the S1 protein of strain TW/97-4 was very similar to that of strains A1211, which belonged to the TW-I serotype that was different from the Massachusetts and Connecticut serotypes [11].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The S1 protein of IBV plays a key role in the induction of protective immune response against IBV and the variation in the S1 sequence is the major mechanism by which a new serotype emerges [2,12]. Phylogenetic analysis showed that the S1 sequences of JP8127, JP8443 and JP9758 are closely related to those of Australian viruses, which have a serotype distinct from the Massachusetts and Connecticut serotypes that have been commonly used as the vaccine [4,8]. Similarly, the S1 protein of strain TW/97-4 was very similar to that of strains A1211, which belonged to the TW-I serotype that was different from the Massachusetts and Connecticut serotypes [11].…”
mentioning
confidence: 99%
“…The S protein is processed into S1 and S2 subunits; the S1 forms the receptor-binding site whereas the S2 anchors the S1 to the viral membrane. Both S1 and N proteins play a critical role in the induction of immune response against IBV and understanding of the S1 and N sequences are important for selection of useful vaccines [2,4,9,12]. However, little information is available on the sequences of the S1 and N genes of Japanese and Taiwanese field strains of IBV [10,11].…”
mentioning
confidence: 99%
“…In contrast, subgroup 2 strains, such as N1/88, cause only mild lesions in the trachea and are associated with minimal signs of respiratory disease (Ignjatovic et al, 1997). Experimental infection of chickens with N1/08 in this study appeared to indicate that the pathogenicity of N1/08 was more similar to that of subgroup 2 strains than subgroup 3 strains.…”
Section: Discussionmentioning
confidence: 66%
“…Historically these strains have been the most prevalent and are associated with lesions in both tracheal and kidney tissues (Ignjatovic et al, 2002;Mardani et al, 2008). Australian subgroup 2 strains were detected between the mid 1980s and early 1990s (Ignjatovic et al, 1997) and have not been reported since, and appear to have emerged from a very different origin and adapted to growth in chickens. Australian Subgroup 2 strains are known to replicate only in the trachea of infected chickens (Ignjatovic et al, 2002;Mardani et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation